2016
DOI: 10.1155/2016/1358593
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Attitudes to Clinical Pain Management and Education: Survey from a Middle Eastern Country

Abstract: Despite promising initiatives to advance the practice of pain management in Middle Eastern countries, their pain care lags behind developed countries. The objectives of this study are to evaluate physicians' assessment of their own competency in pain management, to assess physicians' practice related to pain management, and to identify physician-related barriers to effective pain control. A cross-sectional survey was conducted in 3 teaching medical centers in Lebanon targeting the above-mentioned outcomes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 28 publications
(38 reference statements)
2
15
6
Order By: Relevance
“…The discrepancy between our finding and the aforementioned studies [6,10], may be explained by the absence of regular refresher courses organized in our resource-limited setting to continuously train and update physicians on pain management in the ED.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The discrepancy between our finding and the aforementioned studies [6,10], may be explained by the absence of regular refresher courses organized in our resource-limited setting to continuously train and update physicians on pain management in the ED.…”
Section: Discussioncontrasting
confidence: 99%
“…This may infer that the long years of clinical experience, Cameroonian general practitioners tend to take fewer refresher courses to maintain or upgrade their knowledge on pain management compared to physicians ( residents and interns) undergoing a specialization program. This is in contrast with previous Lebanon cross-sectional study which showed inexperienced physicians to have a lower level of knowledge on pain management [10]. More contradicting results were obtained in an Iranian crosssectional survey which observed a positive and significant correlation between the number of years professional experience and the level of knowledge on pain management (p = 0.002, r = 0.03) [6].…”
Section: Discussioncontrasting
confidence: 79%
“…We also found that there is no relationship between the participating paediatricians' awareness of the LPs and BMAs procedural pain management, their years of clinical experience and their professional title. However, this is obviously contrary to the studies conducted by Kim et al 36 and Nasser et al, 37 which found that the degree of attitude and knowledge status of pain management were correlated with physicians' personal experience. A possible explanation is: no clinical training in pain management and the deficiency of paediatric staff.…”
Section: Open Accesscontrasting
confidence: 71%
“…However, building pain management self‐efficacy among healthcare professionals has remained a challenge because of several barriers. Some of these barriers include lack of training, fear and negative attitudes (Nasser, Nassif, & Saad, ; Yanni et al., ) thus, compromising the effectiveness of treatment modalities and patient safety. Chiang et al.…”
Section: Introductionmentioning
confidence: 99%
“…As competence in pain management is indispensable to ensure effective approaches (Al‐Khawaldeh, Al‐Hussami, & Darawad, ; Craig, ; Yaqoob & Nasaif, ), nurses must engage in continuous professional education to advance knowledge, skills, attitude and self‐efficacy in pain management (Registered Nurses' Association of Ontario (RNAO), ). However, literature also highlighted the importance of exploring the beliefs and attitudes of healthcare professionals (Nasser et al., ; RNAO, ; Wells et al., ; Yaqoob & Nasaif, ). Healthcare professionals with poor knowledge and skills and have negative attitudes towards pain management, especially with opioid analgesics, may ineffectively assess and treat pain (Yanni et al., ).…”
Section: Introductionmentioning
confidence: 99%